2012
DOI: 10.1080/17441692.2012.729220
|View full text |Cite
|
Sign up to set email alerts
|

Drug-scene familiarity and exposure to gang violence among residents in a rural farming community in Baja California, Mexico

Abstract: We examined drug-scene familiarity and exposure to gang violence among residents of a migrant farming community in rural Baja California, Mexico. In October 2010, 164 members of a single colonia (community) underwent an interviewer-administered survey to assess ‘exposure to gang violence’ and ‘drug-scene familiarity’, as well as other health indicators. Logistic regression was used to identify correlates of exposure to gang violence. Overall, 20% of participants were male, the median age was 27 years, 24% spok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…However, in the present study, the presence of a severe drug problem increased the likelihood of that person having committed a crime (Volkmann et al 2013) against persons or property. Other studies have found a relationship of polydrug use, crack or alcohol dependence, and severity of dependence with high rates of crimes against property (Dias et al 2011;Volkmann et al 2013). In a study on the geography of crime in the city of Sao Paulo, crimes against property exhibited an actual growth of 72.6% in the past decade, which was mainly due to the increase in crack use (Souza 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in the present study, the presence of a severe drug problem increased the likelihood of that person having committed a crime (Volkmann et al 2013) against persons or property. Other studies have found a relationship of polydrug use, crack or alcohol dependence, and severity of dependence with high rates of crimes against property (Dias et al 2011;Volkmann et al 2013). In a study on the geography of crime in the city of Sao Paulo, crimes against property exhibited an actual growth of 72.6% in the past decade, which was mainly due to the increase in crack use (Souza 2011).…”
Section: Discussionmentioning
confidence: 94%
“…From there, the information was classified along two dimensions: the nature of the crime (violent or nonviolent) and the target of crime (against the person, property, burglary). This method of classification has been used in prior research (Rodrigues et al 2012;Valdez, Kaplan, and Cepeda 2006;Volkmann et al 2013).…”
Section: Questionnairementioning
confidence: 99%
“…In thinking about 'harm to others' from illicit drugs, two different sources of harm come to mind: first, harm to others can accrue through the illicit drug market and its associated criminal activity [26][27][28][29]. In terms of drug use markets, this harm is largely experienced by community members through either fear of crime, crime itself or costs such as heightened insurance premiums due to crime rates.…”
Section: Application Of Hto To Illicit Drugsmentioning
confidence: 99%
“…In fact, others have found that weak ties to parents, school, and conventional peers increase the probability of the initiation and continuation of deviant behaviors such as drug use and crime (Cepeda, Saint Onge, Nowotny, & Valdez, 2015). Further, it is important to note that others have found that drug scene familiarity and exposure to gang violence are often interconnected (Volkmann et al, 2013). Intervention programs which focus on helping recently released ex-offenders gain a sense of control over positive decision making support the theoretical framework that underpins this study and resonates with the needs articulated by the participants.…”
Section: Discussionmentioning
confidence: 99%